2017
DOI: 10.4236/ojepi.2017.73022
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of High Blood Pressure among Marathon Runners during Beirut-Marathon 2014

Abstract: Objective: To assess the prevalence of high blood pressure (BP) and cardiovascular risk factors among marathon runners during Beirut-Marathon 2014. Methods: A total of 325 marathon runners were divided into 42 km and 10 km groups. They were assessed for cardiovascular risk factors by measuring their BP and answering a questionnaire. The questionnaire composed of 22 questions related to demographic information, risk factors, medical history, family history, medical checkups, use of antihypertensive drugs and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…[6][7][8] At the 2014 Beirut International Marathon it was found that almost one-third of runners were not aware that they had elevated blood pressure and the mobile screening made them aware. 9 Behavioural techniques, sometimes referred to as nudges, can be used to increase people's attendance at scheduled health screenings, for example, by sending letters or text messages with tailored messages. 10,11 Yet, simply increasing people's awareness of their health and access to care cannot increase public health if people informed of their poor health fail to take appropriate action.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] At the 2014 Beirut International Marathon it was found that almost one-third of runners were not aware that they had elevated blood pressure and the mobile screening made them aware. 9 Behavioural techniques, sometimes referred to as nudges, can be used to increase people's attendance at scheduled health screenings, for example, by sending letters or text messages with tailored messages. 10,11 Yet, simply increasing people's awareness of their health and access to care cannot increase public health if people informed of their poor health fail to take appropriate action.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…For example, a positioning screening at a sporting event is one way to make screenings more convenient and can increase awareness of poor health conditions 6‐8 . At the 2014 Beirut International Marathon it was found that almost one‐third of runners were not aware that they had elevated blood pressure and the mobile screening made them aware 9 …”
Section: Introductionmentioning
confidence: 99%